The Influence of Perceived Organizational Support and Rewards on Employee Satisfaction With Employee Performance as a Mediation Variable at Bhayangkara Hospital - Selvi Yona Tamara (Jurnal Manajemen Universitas Bung Hatta, 2023)
Studies on Organizational Support particularly in the sectors of Padang Police Hospitals has gained attention for both academics and practitioners. This study aimed to investigate the impact of employee performance as mediation in support of the organization and respect for employee satisfaction. The sampling technique used in this research is purposive sampling where the number of samples used sebanayk 80 people. Responden.hasil studies have shown that the perceived organizational support has a positive effect on employee satisfaction, rewards positive effect on satisfaction, performance negatively affect satisfaction and performance mediates between perceived organizational support negative effect on employee satisfaction. Specific Ssecara results of this study reveal the performance of mediating between perceived organizational support negative effect on employee satisfaction